Plantas medicinales utilizadas en el tratamiento de enfermedades de la piel en comunidades rurales de la provincia de Los Ríos – Ecuador - Gallegos-Zurita, Maritza (2017)
Introduction: Skin diseases occupy the third place among the ten causes of general morbidity in Ecuador, and traditional medicine practices are the most frequent therapeutic options in rural sectors. Objective: To identify the medicinal plants used for treatment of skin diseases. Design: Descriptive, cross-sectional study. Place: Two rural Babahoyo city parishes named Pimocha and Febres-Cordero, and located south of the Los Ríos province, Ecuador. Participants: Persons responsible for family care consisted in 198 women (61.7%) and 123 men (38.3%), 17 to 76 years old. Interventions: Previous informed consent, direct observations, interviews and surveys were conducted; the U-PlanMed questionnaire was used. Main outcome measures: Plant species and therapeutic uses. Results: Ten species of plants and their therapeutic applications for skin diseases were identified, such as acne, burns, pruritus, rash, dermatitis, ulcerations of the skin (sores), stains, and skin care. Conclusions: 100% of the population used medicinal plants for the treatment of skin conditions, mainly Aloe vera, Chamaemelum nobile, Melissa officinalis and Scoparia dulcis.